Aktivitas Senyawa Antioksidan Ekstrak Kulit Manggis Pada Sosis - Baramula, Andi; Mahmud, Andi Tenri Bau Astuti; Burhan, Hasniar (Universitas Islam Negeri Alauddin Makassar, 2024)
The addition of natural ingredients to sausages improves their quality. Mangosteen rind which contains aromatic substances and antioxidants can be used as a supplement. The aim of this research was to determine the activity of antioxidant compounds from mangosteen peel extract in sausages. This research took place in April 2024 at the Animal Products Technology Laboratory, Hasanuddin University, Biringkanaya District, Makassar City, South Sulawesi, continued with Organoleptic and Antioxidant Tests. This research used a Completely Randomized Design (CRD) consisting of 4 treatments and 3 replications. The samples used in this Antioxidant Test were 4 types of sausages with the addition of mangosteen rind extract consisting of P0 (mangosteen rind extract), P1 (10% mangosteen rind extract), P2 (15% mangosteen rind extract), P3 (20% rind extract mangosteen). Data obtained from the laboratory will be analyzed using ANOVA, and if the results obtained are significant, it will be continued with the Duncan test. Based on the results of the variance analysis that has been carried out, based on the results, the research that has been carried out can be concluded that. Making sausages with the addition of mangosteen peel extract has a significant effect on the hedonic quality test of taste and antioxidants mangosteen peel extract, the higher the level of anti-oxidants it has. Antioxidant levels were found in P3 treatment (21.44).